Design and testing of electrical machines - Deshpande, M.V (PHI Learning, 2010)
The basic theory, principle of operation and characteristics of transformers, three-phase induction motors, single-phase induction motors, synchronous machines and dc machines are dealt with in Appendices to provide the background for the design of these machines.